Spatiotemporal parameters of the operated and non-operated knees before and after unilateral total knee arthroplasty (vol 91, pg 192, 2022 ) - Bilek, Furkan; Deniz, Gulnihal; Esmez, Omer; Belhan, Oktay (Elsevier Ireland Ltd, 2024)
[Abstract Not Available]